A blueprint for the future of professional cycling. Issue 2 (15th March 2018) - Van Reeth, Daam; Lagae, Wim
Abstract : Purpose: Professional road cycling has the capacity to be a major worldwide spectator sport, but has yet, in the eyes of many, failed to realize its full potential. There is a growing awareness that profound reforms are crucial for the sport's future success. The purpose of this paper is to explore the conditions which the sport must address, and define a new business model for professional road cycling. Design/methodology/approach: The paper uses qualitative data to screen professional road cycling's current business model, and to present a coherent vision on the changes needed to reform the sport. Information was gathered from archival material and from talks with stakeholders. Findings: The paper presents a blueprint for the future of professional cycling. It identifies 6 vital building blocks and 25 specific action points, beginning with the idea that professional road cycling needs a stable business model that produces a valuable core product. Originality/value: Professional road cycling is is conservative by nature and changes are extremely difficult to implement. This contribution presents a glimpse of one possible future for professional cycling, if cycling's policy makers acknowledge the need for profound reforms of the sport and are willing to make the necessary changes.